2020
DOI: 10.3390/ijms21186609
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Infection of Aedes aegypti Alters Extracellular Vesicle Protein Cargo to Enhance Virus Transmission

Abstract: Dengue is the most burdensome vector-borne viral disease in the world. Dengue virus (DENV), the etiological cause of dengue, is transmitted primarily by the Aedes aegypti mosquito. Like any arbovirus, the transmission cycle of dengue involves the complex interactions of a multitude of human and mosquito factors. One point during this transmission cycle that is rich in these interactions is the biting event by the mosquito, upon which its saliva is injected into the host. A number of components in mosquito sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The calmodulin gene AAEL012326 is overexpressed in a strain susceptible to dengue compared to one refractory to dengue ( Chauhan et al 2012 ) and produces a protein product that is found in extracellular vesicles produced by Ae. aegypti cells infected by dengue, but not uninfected control cells ( Gold et al 2020 ). The putative 60S ribosomal protein gene AAEL011587 is upregulated in response to chikungunya infection and to chikungunya and dengue coinfection ( Shrinet et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The calmodulin gene AAEL012326 is overexpressed in a strain susceptible to dengue compared to one refractory to dengue ( Chauhan et al 2012 ) and produces a protein product that is found in extracellular vesicles produced by Ae. aegypti cells infected by dengue, but not uninfected control cells ( Gold et al 2020 ). The putative 60S ribosomal protein gene AAEL011587 is upregulated in response to chikungunya infection and to chikungunya and dengue coinfection ( Shrinet et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…aegypti are AAEL001951-PA and actin (Q6QNY2_AEDAE and Q4JQ54_CULPP), with 4.9-and 9.5-fold changes, respectively. All phagocytic activities in mosquitoes involve restructuring the actin cytoskeleton [26,51]. Meanwhile, mosquito cytoplasmic actin has many biological functions, including cell signalling and immunity [52].…”
Section: Discussionmentioning
confidence: 99%
“…EVs have been identified and characterized in many arthropod species, including ticks such as Haemaphysalis longicornis [ 22 ], Ixodes scapularis [ 23 ] and Dermacentor andersoni [ 23 ]. They have also been found in Diptera such as Drosophila [ 24 ] and Aedes aegypti [ 25 ], Ornithoctonus hainana spider [ 26 ], Homarus americanus lobster [ 27 ] and Morpho butterfly [ 28 ]. Tick saliva EVs may facilitate pathogen transmission from arthropods to mammals and participate in tick-host-pathogen relationships [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%